Keamanan dan Kebolehan Tindakan Kedokteran Gigi pada Pasien yang Berpuasa: Tinjauan Literatur - Gita Alivia Ananda; Dwi Kurniawati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Introduction: Ramadan fasting is a religious practice observed by Muslims by abstaining from food and drink from dawn until sunset. These changes may increase the need for oral and dental healthcare. However, some Muslims still perceive that undergoing dental treatment while fasting may invalidate the fast, leading many patients to delay or avoid dental visits during Ramadan. Objective: This study aims to review and analyse various scientific literature regarding the safety and permissibility of dental procedures for patients who are observing fasting during Ramadan. Methods: This study used a narrative review method by searching scientific articles through PubMed, ScienceDirect, and Google Scholar databases using keywords relevant to the research topic. Articles were selected based on predetermined inclusion and exclusion criteria. Results: The review findings indicate that most dental procedures, such as local anaesthesia administration, scaling, restorative treatment, and tooth extraction, generally do not invalidate fasting as long as no material or fluid is intentionally swallowed. The use of suction devices, isolation of the treatment area, and proper scheduling of dental procedures are important factors in minimizing the risk of swallowing fluids during treatment. Conclusion: Most dental procedures can be safely performed on fasting patients while still considering both medical aspects and Islamic principles. Patient education regarding the safety of dental procedures during fasting should be improved to prevent delays in treatment and complications in oral health.